Improving Present Continuous Tense in Writing by Using Total Physical Resonce Method of The Fifth Years Students at SD Negeri 75 PETAN - Evi Purnama Sari; Puspa Gundary; Mohd. Rafi Riyawi (DIMAR: Jurnal Pendidikan Islam, 2021)
The objectives of this study are to improving present continuous tense in writing to the fifth year students of Elementary School using the Total Physical Response (TPR) method and to identify the advantages of using the TPR method in teaching foreign language.To achieve the objectives of the study, the writer conducted an action research. This classroom action research was held at SD Negeri 75 Petani. The subject of the study was the grade V. The action consisted of two cycles. The difference between these cycles was on topic of material used. Each cycle consisted of teaching and learning process and a test. The questionnaire was meant to answer the problems of the study. The analysis of the data showed that there was a significant difference of the students’ achievement in each cycle. The students’ achievement in the cycle II (79 %) was higher than that of cycle I (60,5 %). The relative frequency showed that the mastery level of present continuous tense in the second cycle is better than that on the first cycle. The main factor affecting this improvement was the students’ interest in teaching learning process through Total Physical Response. Based on this data, the writer concluded that teaching present continuous tense through TPR is very beneficial for the students in order to facilitate them in learning present continuous tense. It is suggested that TPR in teaching present continuous tense is recommended for the English teacher.